2000
DOI: 10.1590/s1517-83822000000300007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacteriocins produced by Lactococcus lactis strains

Abstract: Bacteriocins produced by fifteen strains of Lactococcus lactis (14 L. lactis subsp. lactis and one L. lactis subsp. cremoris) were heat resistant, sensitive to several proteolytic enzymes and active over a wide range of pH. Their resistance to the heating was greatly influenced by the pH. Only the strain L. lactis subsp. lactis ITAL 383 produced a bacteriocin with a wide activity spectrum, similar to nisin of L. lactis subsp. lactis ATCC 11454. This bacteriocin inhibited closely related species and other Gram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
6
30
0
3
Order By: Relevance
“…Da mesma forma, Moreno et al (2000), com o intuito de testar a produção de bacteriocinas por Lactococcus, verificaram que o método de antagonismo simultâneo por inoculação em poços permitiu a formação de halos de inibição maiores e mais consistentes. Esse método mostrou ser mais sensível aos métodos de inoculação em forma de pontos e de estrias, pela possibilidade de comparação da concentração de bacteriocinas produzidas pelas diferentes linhagens examinadas.…”
Section: Resultsunclassified
“…Da mesma forma, Moreno et al (2000), com o intuito de testar a produção de bacteriocinas por Lactococcus, verificaram que o método de antagonismo simultâneo por inoculação em poços permitiu a formação de halos de inibição maiores e mais consistentes. Esse método mostrou ser mais sensível aos métodos de inoculação em forma de pontos e de estrias, pela possibilidade de comparação da concentração de bacteriocinas produzidas pelas diferentes linhagens examinadas.…”
Section: Resultsunclassified
“…One example of this second type is nisin, which is produced by certain strains of Lactococcus lactis subsp. lactis (De Vuyst, 1994;Rodriguez, 1996;Moreno et al, 2000). Other is pediocin, produced by Pedicoccus pentosaceus (Moreno et al, 2006).…”
Section: Range Of Activitymentioning
confidence: 99%
“…Bacteria from this group are involved in the production of the lantibiotic nisin, lactococcins, lactostrepcins, diplococcins and others (Mackay et al, 1997;Moreno et al, 2000). Cheigh et al (2004) have developed a simple onestep purification method, using expanded bed ionexchange chromatography, for the fractionation of nisin Z produced by Lactococcus lactis subsp.…”
Section: Purification Of Class I Bacteriocinsmentioning
confidence: 99%
“…Some authors differentiate nisin from other lactococcal bacteriocin by the fact that α-chymotrypsin is the only proteolytic enzyme to which nisin is sensitive (14,22). Nevertheless, this property is to be regarded with caution, since other authors have reported that nisin can also be inactivated by other enzymes such as pronase E (15,23), and ficin (5,21).…”
Section: Sensitivity To Proteolytic and Lipolytic Enzymesmentioning
confidence: 99%